Optimization of Probiotic Drinks Fermentation in Bidara (Ziziphus mauritiana) Fruit Juice with Lactobacillus plantarum InaCC B616 using Response Surface Methodology - Subkhan Subkhan; Ernawati Sinaga; Safendrri Komara Ragamustari; Endang Sukara (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2025)
Bidara fruit (Ziziphus mauritiana) is known to contain various bioactive phytochemicals, including phenolic acid, ascorbic acid, saponins, terpenoids, flavonoids, and tannins, making it highly promising for development into functional beverage products. Several studies state that fermentation with probiotic bacteria can improve the functional properties of products. This research aims to optimize the fermentation process of bidara fruit juice with Lactobacillus plantarum InaCC B616 using Response Surface Methodology and determine the effect of fermentation time on the content of bioactive compounds such as total phenols, total flavonoids, antioxidant capacity, and inhibition of the α-glucosidase enzyme. Optimization of fermentation was carried out using a Central composite design with 13 experimental samples and test data using Design Expert® 13 software, the optimization of fermentation time was conducted using a Completely Randomized Design (CRD) with four treatment groups and three replications per group, including a negative control treatment: no fermentation (F0), fermentation for 12 hours (F1), fermentation for 24 hours (F2), and fermentation for 48 hours (F3). The research results showed that 18.61% bidara fruit juice and 0.34% skim milk was the optimum formula for fermenting bidara fruit juice. The best fermentation duration was in the F3 group (fermentation for 48 hours), in this group the bacterial growth reached 3.1x109 cfu/mL with a total phenolic compound content of 81.80 mg GAE/mL, total flavonoids 2.81 mg QE/g, capacity antioxidant 99.28 µg AAE/mL, and inhibition of the α-glucosidase enzyme 87.42%. The fermentation of bidara fruit juice with Lactobacillus plantarum InaCC B616 has the potential to enhance total phenol content, total flavonoids, antioxidant capacity, and α-glucosidase enzyme inhibition, making it a promising candidate for probiotic beverages. This drink could be developed as an alternative treatment for type 2 diabetes mellitus due to its inhibitory activity against the α-glucosidase enzyme.